Trends in the Global Petroleum Industry - Balasundram Maniam; Todd Robbins; Geetha Subramaniam (International Journal of Supply Chain Management, 2017)
The petroleum industry provides the largest source of energy needs across the global world. As a result many economies are heavily influenced by the petroleum industry. The Organization of Petroleum Exporting Countries (OPEC) has a significant market share and strives to influence crude oil pricing to help support their interests. Recent trends in the petroleum industry have seen the influence of OPEC diminish. The extent to which OPEC can influence the crude oil market as well as the motivations behind their decisions are explored in this research. Evidence is presented that OPEC does not meet the strict definition of a cartel but they still have an impact on the market. Their actions have components of profit maximization and political motivations. When OPEC makes a decision to alter production levels, particularly with a cut or maintain position, it has an overall impact on crude oil pricing. Dramatic swings in crude oil pricing, referred to as oil price shocks, have macroeconomic impacts on stock markets and other economic measures both domestically as well as globally. Predicting future oil prices is challenging. This paper looks at various methodologies used in trying to explain and forecast future crude oil prices.